Maggot Cultivation Training as Alternative Feed in Fish Cultivation for Indonesian Migrant Workers at PCIM Kuala Lumpur, Malaysia: Pelatihan Budidaya Maggot sebagai Pakan Alternatif dalam Budidaya Ikan bagi Pekerja Migran Indonesia di PCIM Kuala Lumpur, Malaysia - Dini Siswani Mulia; Suwarsito; Sri Wahyuni; Ratna Kartika Wati; Sugeng Priyadi (Altifani Journal: International Journal of Community Engagement, 2025)
The Special Branch of Muhammadiyah Malaysia accommodates Indonesian Migrant Workers (IMW) from the Kampung Bharu, Kampung Pandan, and Kepong areas. The main problem that arises for IMW is the economy. One activity that can help the IMW economy in Malaysia is entrepreneurship through fish farming. Freshwater fish farming has good prospects for development and can be used as a source of income. However, feed costs can reach 60-70% of fish production costs, so it is necessary to find alternatives to replace commercial feed with good nutritional quality and lower prices, including maggots. This activity aims to improve the knowledge and skills of partners in cultivating maggots as an alternative feed in fish farming. This activity is research-based community empowerment as a transfer of knowledge and technology to target partners to improve knowledge and skills about maggot farming. Community service activities are carried out using participatory and collaborative approaches; partners actively participate in activities and collaborate. Community service activities are carried out in 5 stages: coordination of activity preparation with partners, counseling on maggots, potential and how to cultivate them, maggot farming training, mentoring, and activity evaluation. The program's success rate was measured using the one-group pre-test and post-test. The results of the activity showed that 85% of partner members understood the potential of maggots and how to cultivate them from the previous 52.5% (exceeding the target of 80%); 85% were able to implement maggot cultivation from the previous 40% (exceeding the target of 80%). The evaluation showed that this community service activity could help partners overcome the problem of providing cheap and potential alternative fish feed and fish cultivation problems. Based on the evaluation, there needs to be a continuation of the program to assist partners in overcoming various problems to improve the economy, one of which is through fish cultivation.